OʻZBEKISTONDA BANK XIZMATLARINI KOʻRSATISH KOʻLAMINI KENGAYTIRISH YOʻLLARI - Ibroximov Ilxomjon Shavkatjon o’g’li, Xikmatov Izzatilla Qudratilla o’g’li (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article is considering expanding the scope of banking services of commercial banks operating in Uzbekistan. As part of the study, the author analyzed practical data from commercial banks. Based on the results obtained, existing problems in expanding the scope of banking services of commercial banks and developing proposals for their elimination were identified.